Positron-helium scattering: Resonance and differential cross sections - Chaudhuri, Puspitapallab; Adhikari, Sadhan K. [UNESP] (Elsevier, 1998)
We study positron-helium scattering using close coupling approximation (CCA) employing different combinations of the following basis functions: He(1s1s), He(1s2s), He(1s2p), Ps(1s). and Ps(2s), where Ps stands for the positronium atom. We observe a prominent S wave resonance of width 2 eV at about 30 eV, in excitation and rearrangement cross sections to He(1s2s), He(1s2p), Ps(1s) and Ps(2s) states. We also report results of differential cross sections for the excitation of helium and positronium formation.